(untitled) (Journal of Enam Medical College, 2012)
Congenital tuberculosis is an unusual and severe clinical presentation of Mycobacterium tuberculosis (MTB) infection. It is usually difficult to diagnose and treat. We report a tenweek-old male infant who had presented with fever, difficulty in breathing, abdominal distension, convulsion, low weight gain since one month of his age. The diagnosis was made by demonstration of MTB bacilli in the gastric aspirate of baby and chest radiography. Treatment with the four drug regimen including streptomycin was initiated, but the baby died on the third day of ATT. This case gives an account of difficulties in diagnosis and therapeutic management of congenital tuberculosis and alerts for development of protocols that foresee these difficulties. DOI: http://dx.doi.org/10.3329/jemc.v1i2.11469 J Enam Med Col 2011; 1(2): 85-87